Sistem Penyimpanan Bahan Makanan Segar dan Kering di RS Pusri Palembang Berdasarkan Suhu Penyimpanan - Sihite, Nathasa; Antisa, Putri Salsabila; Sriwiyanti, Sriwiyanti; Hartati, Yuli; Rotua, Manuntun (Jurnal Pustaka Padi (Pusat Akses Kajian Pangan dan Gizi), 2024)
Maintenance of hospital food is a crucial set of tasks encompassing various facets such as menu planning, determining food requirements, budgeting, procurement, reception, storage, food processing, distribution, documentation, reporting, and evaluation. This study aims to provide a descriptive overview of the storage system for both fresh and dry food ingredients at Pulri Palembang Hospital's Nutrition Facility, assessing whether it aligns with established hospital nutrition guidelines. The methodology employed in this research involves descriptive analysis, offering a comprehensive portrayal of the food storage system with a focus on storage temperature. Findings indicate that while the storage system for dry and fresh food items at the Pusri Palembang Clinic's Nutrition Facilities largely adheres to storage standards, certain aspects, particularly concerning the storage temperature of dry food items, fall short of meeting the PGRS standard criteria. For instance, the recommended temperature range is between 19 and 21 °C, whereas the average temperature for dry storage at the Pusri Clinic is approximately 23 °C. Additionally, the survey results reveal a lack of periodic monitoring of maximum temperature controls. This study underscores the importance of implementing regular checks to monitor the temperature of dry food items. Despite dry food's relative resilience to spoilage, maintaining optimal quality necessitates temperature control within the recommended range of 19 to 21 °C.